Student Motivation on Physical Education Learning For Senior High School - Sovie Ogi Mayolla Mayolla; Leni Apriani (INSPIREE: Indonesian Sport Innovation Review, 2023)
The  purpose  of  the study. The aim of this research is to find out the students' motivation towards learning physical education at senior high school. Materials and methods. This type of research is quantitative descriptive research. According to Sugiyono (2014) Quantitative method is a scientific method because it has fulfilled scientific principles, namely concrete, objective, measurable, rational, and systematic so that it is suitable for use for proof or confirmation. Results. The results showed that the categories (1) Duration of learning activities with an average of 62%, (2) Frequency of learning activities 58%, (3) Presentation of learning activities 66% (4) Perseverance to achieve learning objectives 61% (5) Devotion to achieve the learning objectives 62% (6) The level of appreciation to be achieved is 67% (7) The level of qualification for learning achievement is 70% (8) The direction of the attitude towards the target of learning activities is 57%. Conclusions. Based on data processing and data analysis, the conclusions in this study are Student Motivation towards Physical Education Learning in Class at senior high school SENIOR Negeri 1 Sungai Apit with an average of 63% in the strong category.